Productivity as the main factor correlating with migratory behaviour in the evolutionary history of warblers. (8th July 2018) - Ponti, R.; Arcones, A.; Ferrer, X.; Vieites, D. R.
Abstract: The evolution of migration in birds and its causes are still subject of debate. Recent studies tracking current bird migration have identified peaks in net primary productivity (NPP) as a main driver of bird migratory behaviour. However, it is unclear which variables may have played a major role in the evolution of bird migration at deeper phylogenetic levels. Here, we used phylogenetic comparative methods to assess whether the evolutionary patterns of migratory distances, as a proxy for migratory behaviour, are correlated with several biometric, climatic and productivity variables in a phylogenetic context, using Sylvia warblers as a case study. Our results recover NPP in the breeding range and during the breeding season as the variable with stronger positive correlation with migratory distances, being always included in the best models considering all potential variables. Several climatic variables show a correlation with the evolution of migration, but those are also tightly correlated with NPP. Among morphological variables, migratory lineages tend to have longer wings than sedentary ones. Although NPP has been identified as a driver of migratory behaviour in current species, in a phylogenetic scale it is not possible to disentangle if it was a main driver in the evolution of bird migratory behaviour or a consequence of it, yet migration and NPP seem to be tightly related today and along the long evolutionary history of these passerines. Abstract : The evolution of migration in birds and its causes are still subject to debate. It is unclear which variables may have played a major role in the evolution of bird migration at deeper phylogenetic levels. Here, we used phylogenetic comparative methods to assess whether the evolutionary patterns of migratory distances, as a proxy for migratory behaviour, are correlated with several biometric, climatic and productivity variables in a phylogenetic context, using Sylvia warblers as a case study. Our results recover Net Primary Productivity (NPP) in the breeding range and during the breeding season as the variable with stronger positive correlation with migratory distances. Migration and NPP seem to be tightly related today and along the long evolutionary history of these passerines.